An improved public auditing protocol for cloud storage integrity checking. (4th July 2019) - Zhang, Jindan; Wang, Baocang
Nowadays, cloud storage is a popular service for many data owners, they prefer to outsource their datum to the cloud servers. However the cloud servers maybe sometimes loss datum due to accidents. Thus, the integrity of the outsourced datum need to be ensured by the data owners or even any other third parties publicly. Recently in the mobile cloud computing setting, Chen et al. proposed a public auditing protocol for data integrity based on adjacency-hash-table. However we find the data blocks' tags can be easily forged in their proposal, and thus the cloud servers can loss datum but still has the ability to give correct proof for data position, which breaks the security of their proposal. We show two concrete attacks to their proposal and give an improved public auditing protocol for cloud storage integrity checking and roughly analysis its security.